2007
DOI: 10.1007/s00213-007-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin2C receptor agonist Ro-60-0175 attenuates effects of nicotine in the five-choice serial reaction time task and in drug discrimination

Abstract: The data suggest that selective occupancy of 5-HT(2C) receptors can attenuate some effects of nicotine in the 5-CSRTT and weaken the nicotine discriminative stimulus; these effects cannot be explained by a sedative action of Ro-60-0175.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 61 publications
(97 reference statements)
5
18
0
Order By: Relevance
“…Although lorcaserin did not engender nicotine appropriate responding, it did diminish the discriminative stimulus property of nicotine. Similar findings have been reported for other 5-HT 2C receptor agonists, Ro 60-0175 and WAY-163909 (Quarta et al, 2007;Zaniewska et al, 2007), confirming that 5-HT 2C receptor activation weakens the nicotine cue. In contrast to the stimulant and reinforcing effects, the contribution of DA mechanisms to the discriminative stimulus effects of nicotine is less clear Desai et al, 2003;Smith and Stolerman, 2009), and neuroanatomically sites distinct to the mesolimbic DA pathway appear to contribute to the cue, with nicotine infusions into the prefrontal cortex producing the most reliable generalization of the sites examined (Miyata et al, 2002;Smith and Stolerman, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although lorcaserin did not engender nicotine appropriate responding, it did diminish the discriminative stimulus property of nicotine. Similar findings have been reported for other 5-HT 2C receptor agonists, Ro 60-0175 and WAY-163909 (Quarta et al, 2007;Zaniewska et al, 2007), confirming that 5-HT 2C receptor activation weakens the nicotine cue. In contrast to the stimulant and reinforcing effects, the contribution of DA mechanisms to the discriminative stimulus effects of nicotine is less clear Desai et al, 2003;Smith and Stolerman, 2009), and neuroanatomically sites distinct to the mesolimbic DA pathway appear to contribute to the cue, with nicotine infusions into the prefrontal cortex producing the most reliable generalization of the sites examined (Miyata et al, 2002;Smith and Stolerman, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, nicotine reliably increased premature responding and lorcaserin (0.3-1 mg/kg) significantly reduced this measure to baseline levels, without significantly disrupting a principal measure of choice accuracy (see also Quarta et al, 2007 with respect to Ro 60-0175). A feature of all 5-HT 2C agonists tested to date is that premature responding as measured in the 5-CSRTT is particularly sensitive to modulation by this class (Quarta et al, 2007;Fletcher et al, 2007;Navarra et al, 2008;present study). The small effects of lorcaserin (1 mg/kg) to increase omissions and response latencies may be partially attributable to its anorectic effects as they are qualitatively similar to those seen after prefeeding rats prior to the task (eg, .…”
Section: Discussionmentioning
confidence: 99%
“…In line with these studies, the increase in morphine-induced DA release in the NAcc was inhibited by stimulation of 5-HT 2C receptors in freely moving rats [ 96 ]. Furthermore, DA release in the NAcc and corpus striatum, in addition to the DA neuronal fi ring rate in the VTA and the substantia nigra pars compacta (SNc) induced by morphine, was enhanced by SB 206553 administration [ 128 ]. The effects of these agonists were blocked by SB 242084.…”
Section: -Ht 2c Receptorssupporting
confidence: 57%
“…The ability of M100907 and Ro60-0175 to dosedependently reduce the NMDA antagonists-induced premature responding (impusivity) is consistent with previous findings showing similar effects after systemic or intramPFC injections of these compounds (Calcagno et al 2009;Carli et al 2006;Higgins et al 2003;Mirjana et al 2004). Decreased premature responding in normal rats was also reported after systemic M100907 and Ro60-0175 (Fletcher et al 2007;Quarta et al 2007) but also when M100907 was administered in the mPFC or nucleus accumbens (NAc) (Robinson et al 2008;Winstanley et al 2003). The fact that in some studies M100907 did not reduce significantly rats' premature responding under basal task conditions may be due to the low number of responses made when the intertrial interval was 5 s (floor effect) (Mirjana et al 2004;Robinson et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…The 5-HT 2A , but not 5-HT 1A , receptors appear particularly involved in impulsivity (Carli and Samanin 2000;Koskinen et al 2000a, b;Passetti et al 2003;Quarta et al 2007;Robinson et al 2008;Ruotsalainen et al 1997;Winstanley et al 2003Winstanley et al , 2004a. In addition, we have shown that systemic or intra-mPFC administration of 5-HT 2A receptor antagonist M100907 or systemic administration of the 5-HT 2C receptor agonist Ro60-0175, reverse intra-mPFC CPPinduced impairment in attentional functioning and impulsivity but not perseverative responding whereas activation of 5-HT 1A receptors in the mPFC reverses the deficit in accuracy and perseverative responding but not the impulsive premature responses (Calcagno et al 2009;Carli et al 2006;Mirjana et al 2004).…”
Section: Introductionmentioning
confidence: 98%